2010
DOI: 10.4236/jbise.2010.34058
|View full text |Cite
|
Sign up to set email alerts
|

The opinion and experience of surgeons with laparoscopic bowel grasper haptics

Abstract: Background: In order to develop new and better laparoscopic bowel instruments, which reduces patient risks, the opinions and experience that surgeons have with current laparoscopic bowel grasper haptics is important. In this study we explored this by means of a questionnaire. Method: A total of 386 online- questionnaires, were sent to laparoscopic surgeons working in European hospitals. They were all members of the European Association of Endoscopic Surgery and perform laparoscopic obesities or bowel surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Future studies will focus on enhancing the firm grip of the chamber-gripper devices while maintaining a soft compliant grip, which can be attained through modifying the grip contact surfaces with features, such as teeth, to improve grip performance. Moreover, a prior study conducted by Van der Putten et al [14] found that 77% of European surgeons favored tactile feedback as an indication for the level of applied pinch force. Hence, tactile sensors could be integrated into the soft pneumatic chamber-gripper devices by embedding force sensors such as strain-sensitive fibers/sheets, into the inner walls of the gripper component so as to detect the level of force that is applied onto the object being gripped.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will focus on enhancing the firm grip of the chamber-gripper devices while maintaining a soft compliant grip, which can be attained through modifying the grip contact surfaces with features, such as teeth, to improve grip performance. Moreover, a prior study conducted by Van der Putten et al [14] found that 77% of European surgeons favored tactile feedback as an indication for the level of applied pinch force. Hence, tactile sensors could be integrated into the soft pneumatic chamber-gripper devices by embedding force sensors such as strain-sensitive fibers/sheets, into the inner walls of the gripper component so as to detect the level of force that is applied onto the object being gripped.…”
Section: Discussionmentioning
confidence: 99%